2017
DOI: 10.3390/nu9020155
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Long Chain n-3 Polyunsaturated Fatty Acids and Autism Spectrum Disorder: Systematic Review and Meta-Analysis of Case-Control and Randomised Controlled Trials

Abstract: Omega-3 long chain polyunsaturated fatty acid supplementation (n-3 LCPUFA) for treatment of Autism Spectrum Disorder (ASD) is popular. The results of previous systematic reviews and meta-analyses of n-3 LCPUFA supplementation on ASD outcomes were inconclusive. Two meta-analyses were conducted; meta-analysis 1 compared blood levels of LCPUFA and their ratios arachidonic acid (ARA) to docosahexaenoic acid (DHA), ARA to eicosapentaenoic acid (EPA), or total n-6 to total n-3 LCPUFA in ASD to those of typically dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 126 publications
(383 reference statements)
2
78
0
3
Order By: Relevance
“…Polyunsaturated fatty acids (PUFAs), especially omega-3, play significant roles in the structure, function, and development of human brains [Freeman et al, 2006;McNamara & Carlson, 2006;Rombaldi Bernardi, de Souza Escobar, Ferreira, & Pelufo Silveira, 2012]. Differential PUFA status in individuals with versus without ASD [Brigandi et al, 2015;Jory, 2016;Wiest, German, Harvey, Watkins, & Hertz-Picciotto, 2009;Yui, Imataka, Kawasaki, & Yamada, 2016], and small studies of fatty acid supplementation to improve ASD symptoms were recently reviewed [Mazahery et al, 2017]. Omega-3 consumption during pregnancy has been associated with higher IQ [Richardson, Easton, & Puri, 2000b] and fewer social problems [Richardson & Ross, 2000].…”
Section: Ipimentioning
confidence: 99%
“…Polyunsaturated fatty acids (PUFAs), especially omega-3, play significant roles in the structure, function, and development of human brains [Freeman et al, 2006;McNamara & Carlson, 2006;Rombaldi Bernardi, de Souza Escobar, Ferreira, & Pelufo Silveira, 2012]. Differential PUFA status in individuals with versus without ASD [Brigandi et al, 2015;Jory, 2016;Wiest, German, Harvey, Watkins, & Hertz-Picciotto, 2009;Yui, Imataka, Kawasaki, & Yamada, 2016], and small studies of fatty acid supplementation to improve ASD symptoms were recently reviewed [Mazahery et al, 2017]. Omega-3 consumption during pregnancy has been associated with higher IQ [Richardson, Easton, & Puri, 2000b] and fewer social problems [Richardson & Ross, 2000].…”
Section: Ipimentioning
confidence: 99%
“…Omega-3 Omega-3 fatty acids have anti-inflammatory and immunomodulatory properties [151][152][153]. Supplementation with omega-3 decreases NF-κB, IL-12, and IL-13 gene expression [154], and levels of macrophage inflammatory protein (MIP)-2, IL-6 [155], IL-17A [156], and TNF-α [155][156][157][158].…”
Section: Supplementsmentioning
confidence: 99%
“…Supplementation with omega-3 decreases NF-κB, IL-12, and IL-13 gene expression [154], and levels of macrophage inflammatory protein (MIP)-2, IL-6 [155], IL-17A [156], and TNF-α [155][156][157][158]. Despite being widely used as an alternative practice in children with ASD [159,160], omega-3 supplementation cannot be recommended based on the evidence that is currently available [151,[160][161][162][163][164].…”
Section: Supplementsmentioning
confidence: 99%
“…It is generally agreed that ASD is driven by an interaction between genetic and non-genetic factors (such as nutritional factors) [25]. There is some data to support a role for vitamin D and omega-3 long chain polyunsaturated fatty acids (LCPUFA), especially eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), in the development and management of ASD, though the findings are mixed [26,27]. These nutrients have immunomodulatory, anti-inflammatory and anti-oxidant properties, and both have important roles in brain function and structure and in the neurotransmitter system [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of vitamin D and omega-3 LCPUFA in improving ASD-related symptoms has been tested in a few randomised controlled trials. However, the results from these trials are mixed and inconclusive [26,27]. Using the Social Responsiveness Scale (SRS) (total and domains) questionnaire, our research group previously investigated the effect of vitamin D, omega-3 LCPUFA or both on core symptoms of ASD (VIDOMA trial) and also found mixed results [43].…”
Section: Introductionmentioning
confidence: 99%